Use of high-dosage chemotherapy with autologous hematopoietic stem cell transplantation as a first-line therapy for the patients with poor-prognosis testicular tumors - Marjanović Slobodan; Cerović Snežana; Brajušković Goran R. (Vojnosanitetski Pregled)
Background. High-dose chemotherapy followed by hematopoietic stem cell support can be used as a first-line treatment in patients with germ-cell tumor (GCT) with poor prognosis. Long-term survival rate is attained in 50% of these patients. The aim of this paper was to present the experience at the Department of Hematology, Military Medical Academy, with high-dose cytostatic therapy as first-line chemotherapy in GCT patients with poor prognosis. Methods. Between 1997 and 2003, five patients with high-risk germ-cell tumors were treated with high-dosage chemotherapy followed by an autologous stem cell transplantation. All the patients were with non-seminomatous germ-cell tumors with mixed histology, and one was with extragonadal retroperitoneal germ-cell tumor. Results. The follow-up period ranged from 8 to 33 months. Three patients achieved complete remision, two patients only partial remision, and one was not followed-up. One patient was with residual tumor resection, using retroperitoneal lymphadenectomy, after autologous stem cell transplantation. All the patients were treated according to standard protocols. Conclusion. Early high-dose chemotherapy associated with hematopoietic stem cell support as a first-line treatment in the patients with germ-cell tumor with a poor prognosis, represented an efficient treatment modality.